Magnetic Structure and Propagation of Two Interacting CMEs From the Sun to Saturn. Issue 11 (3rd November 2021) - Palmerio, Erika; Nieves‐Chinchilla, Teresa; Kilpua, Emilia K. J.; Barnes, David; Zhukov, Andrei N.; Jian, Lan K.; Witasse, Olivier; Provan, Gabrielle; Tao, Chihiro; Lamy, Laurent; Bradley, Thomas J.; Mays, M. Leila; et al.
Abstract: One of the grand challenges in heliophysics is the characterization of coronal mass ejection (CME) magnetic structure and evolution from eruption at the Sun through heliospheric propagation. At present, the main difficulties are related to the lack of direct measurements of the coronal magnetic fields and the lack of 3D in‐situ measurements of the CME body in interplanetary space. Nevertheless, the evolution of a CME magnetic structure can be followed using a combination of multi‐point remote‐sensing observations and multi‐spacecraft in‐situ measurements as well as modeling. Accordingly, we present in this work the analysis of two CMEs that erupted from the Sun on April 28, 2012. We follow their eruption and early evolution using remote‐sensing data, finding indications of CME–CME interaction, and then analyze their interplanetary counterpart(s) using in‐situ measurements at Venus, Earth, and Saturn. We observe a seemingly single flux rope at all locations, but find possible signatures of interaction at Earth, where high‐cadence plasma data are available. Reconstructions of the in‐situ flux ropes provide almost identical results at Venus and Earth but show greater discrepancies at Saturn, suggesting that the CME was highly distorted and/or that further interaction with nearby solar wind structures took place before 10 AU. This work highlights the difficulties in connecting structures from the Sun to the outer heliosphere and demonstrates the importance of multi‐spacecraft studies to achieve a deeper understanding of the magnetic configuration of CMEs. Key Points: We analyze the eruption of two coronal mass ejections on April 28, 2012 and their evolution up to Saturn We study and compare the flux rope magnetic structure at the Sun, at Venus, at Earth, and at Saturn We find a single flux rope structure at all planets, suggesting interaction of the two eruptions in the inner heliosphere